Association between weight-adjusted waist index and kidney stones: a propensity score matching study - Chen, Di; Xie, Yurun; Luo, Quanhai; Fan, Wenji; Liu, Gang (Frontiers in Endocrinology, 2024)
Objective: This study aimed to investigate the association between weight-adjusted waist index (WWI), a novel adiposity index, and kidney stone (KS). Methods: Data were obtained from the National Health and Nutrition Examination Survey (NHANES) 2007-2018. According to the history of KS, participants were divided into the non-stone group and the stone group. Weighted multivariable logistic regression analyses were used to evaluate the correlation between WWI and KS in unadjusted, partially adjusted, and all-adjusted models. A restricted cubic spline (RCS) analysis assessed the association between continuous WWI and KS risk and obtained the risk function inflection point. Then, subgroup analysis based on the risk function inflection point was conducted to dissect the association in specific subgroups. In addition, the above analyst methods were repeatedly performed in populations after propensity score matching (PSM). The receiver operating characteristic (ROC) curve was applied to compare the ability to predict KS occurrence among WWI, visceral adiposity index (VAI), and body mass index (BMI).Results: Weighted multivariable logistic regression analyses found a positive association between continuous WWI and KS risk in the all-adjusted model [OR=1.03, 95% confidence interval (CI):1.02-1.04, P<0.001]. In further analysis, the Q4 WWI group was linked to the highest KS risk when compared to the Q1-Q3 group (OR=1.06, 95% CI:1.05-1.08, P<0.001). RCS analysis found a linear significant correlation between continuous WWI and KS risk, and the risk function inflection point is 11.08 cm/√kg. Subgroup analysis confirmed that WWI was associated with KS risk in different groups. After PSM, increased WWI was still related to a high risk of KS.Moreover, the ROC curve demonstrated that WWI has a higher predictive ability of KS occurrence than VAI and BMI (Area Under Curve: 0.612 VS 0.581 VS 0.569).Conclusion: In the US adult population, elevated WWI value was associated with an increased risk of KS. Furthermore, WWI was a better predictor of KS occurrence than VAI and BMI.